Letter : International Solidarity Fund - Schevenels, Walther, b. 1894
030-0127-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter F.I. de Sol No.174 Sch/G. 29th June, 1938. Mr. H. V. Tewson, Assistant Secretary, Trades Union Congress General Council Transport House London S.W.1. Dear Comrade Tewson, INTERNATIONAL SOLIDARITY FUND. I duly received your communication of the 29th June regarding the consignment of dried cod and soap and of the 5,600 pairs of sandals and 300 dozen pairs of socks. I have informed Santiago accordingly. As to your other letters regarding the latest figures of our International Solidarity Fund in respect to the relief action in Spain and in China, I hope to find the necessary time before the end of the week to compile all information in my possession and to let you know. Yours fraternally, W. Schevenels, General Secretary. 292/946/30/127